2003
DOI: 10.1038/sj.ejcn.1601714
|View full text |Cite
|
Sign up to set email alerts
|

Birth weight, growth and feeding in infancy: relation to serum lipid concentration in 12-month-old infants

Abstract: Objective: To assess the effects of birth size, growth and feeding in infancy on serum lipids in 12-month-old infants. Design: A longitudinal observation study on infants' consumption and growth. Food and growth records were made every month. At 6, 9 and 12 months, food records were weighed to calculate intake. Serum total cholesterol (TC), high-density lipoprotein-cholesterol (HDL), low-density lipoprotein (LDL) -cholesterol and triglyceride concentrations were analysed at 12 months. Settings: Birth and growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 36 publications
2
18
1
Order By: Relevance
“…Differences in dietary fat intake on the one hand and serum lipid levels on the other, between this study and published data from Finland (Lagström et al, 1997;Simell et al, 2000) and Iceland (Thorsdottir et al, 2003) were tested using reported means, s.d.s and sample sizes. For Icelandic infants, the calculations of P:S and U:S were made from mean values given in the original paper (Thorsdottir et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Differences in dietary fat intake on the one hand and serum lipid levels on the other, between this study and published data from Finland (Lagström et al, 1997;Simell et al, 2000) and Iceland (Thorsdottir et al, 2003) were tested using reported means, s.d.s and sample sizes. For Icelandic infants, the calculations of P:S and U:S were made from mean values given in the original paper (Thorsdottir et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…For Icelandic infants, the calculations of P:S and U:S were made from mean values given in the original paper (Thorsdottir et al, 2003). The significance level was set at P o0.05.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations